(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, we will consider the possibilities of developing the market of insurance services through the formation of modern insurance services. The article analyzes the methods of using world experience in the formation of modern insurance services and the experience and paths of countries with developed insurance services in the world.